Address Presenting the First Annual Report - Meyer, Eugene (World Bank, Washington, DC, 2019)
Eugene Meyer, President of the International Bank for Reconstruction and Development, presented the First Annual Report by the Executive Directors to the Board of Governors. The report had its genesis over three years during a war in which nearly all mankind was engaged. Meyer details the happenings from 1944 to 1946 and the founding of the organization. The Bank was created to assist in the reconstruction and development of its members by investing capital for productive purposes. Key personnel have been appointed, and working procedures developed. The Bank commenced formal operations on June 25th. Loan requests have been received from two countries. Meyer expects to be lending large sums of money. The goal is to promote peace and prosperity through monetary stabilization and the restoration of international credit, thereby improving the lot of humanity.